Structure and Optical Properties of B’- Phase of Ag8SnSe6 - Semkiv І.V. (Physics and Chemistry of Solid State, 2016)
Energy dispersive x-ray spectroscopy of lowtemperature b¢-Ag8SnSe6 crystalcarried out. Energy dispersive spectrum shows only peaks related to Ag8SnSe6. Experimental optical absorption spectrum and band gap value 0.82 eV are determined. Theoretical calculation of absorption spectrum shows good agreement with experimental studies. Modeling of crystal structure of Ag8SnSe6 argyrodite and interatomic distances calculation are carried out.